Phase 2 trial of afatinib, an ErbB family blocker, in solid tumors genetically screened for target activation. Issue 16 (14th June 2013) - Kwak, Eunice L.; Shapiro, Geoffrey I.; Cohen, Seth M.; Becerra, Carlos R.; Lenz, Heinz‐Josef; Cheng, Wen‐Fang; Su, Wu-Chou; Robohn, Meghan; Le Maulf, Florence; Lobmeyer, Maximilian T.; Chand, Vikram K.; Iafrate, A. John
<x xml:space="preserve">Abstract</x> BACKGROUND The efficacy of afatinib, an irreversible ErbB Family Blocker, was evaluated in patients who had 1 of 4 categories of solid tumors with epidermal growth factor receptor/human epidermal growth factor receptor 2 (EGFR/HER2) gene amplification or EGFR‐activating mutations. METHODS Patients with previously treated but ErbB inhibitor‐naive esophagogastric, biliary tract, urothelial tract, or gynecologic cancers (lung cancers were excluded) harboring EGFR/HER2 gene amplification or high polysomy were identified by fluorescence in situ hybridization (FISH). Tumors were also screened for EGFR mutations. The primary endpoint was the objective response rate; secondary endpoints included the clinical benefit rate, pharmacokinetics, and safety. RESULTS Of 385 prescreened patients, 38 had FISH‐positive tumors (10 with EGFR amplification and 29 with HER2 amplification or high polysomy [1 tumor had EGFR/HER2 high polysomy]; none had EGFR‐activating mutations), and 20 patients received treatment with afatinib 50 mg daily. The objective response rate was 5% (1 of 20 patients), and the best objective response included 1 complete response. Eight patients experienced stable disease. The most frequently reported adverse events were diarrhea, rash, and decreased appetite. The trial closed early because of slow recruitment. CONCLUSIONS Single‐agent afatinib activity was limited, yet encouraging, in selected tumors that were screened prospectively for target activation. The implementation of a biomarker‐driven approach using a low‐frequency biomarker for patient selection across multiple tumor types can be challenging. Cancer 2013;119:3043—3051. © 2013 American Cancer Society.